2015
DOI: 10.17269/cjph.106.4839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, co-occurrence and decennial trends of family violence toward children in the general population

Abstract: OBJECTIVES: In Quebec, three population-based surveys have documented the prevalence of psychological aggression, and minor and severe physical violence toward children. This paper aims to present 1) the results of the 2012 survey with regard to the frequency and annual prevalence of violence, and 2) the trends in all three forms of violence between 1999 and 2012 according to children's age. METHODS:The three independent surveys were all conducted through telephone interviews in 1999, 2004 and 2012 by the Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To our knowledge, there is no data on family bullying, as defined in this study, in Canada. Clément et al (2015) found that about 50% of mothers reported repeated family violence toward their children over a one-year period. However, the children in their study were much younger (aged 0 to 18 years old), which is usually associated with higher rates of family victimization.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no data on family bullying, as defined in this study, in Canada. Clément et al (2015) found that about 50% of mothers reported repeated family violence toward their children over a one-year period. However, the children in their study were much younger (aged 0 to 18 years old), which is usually associated with higher rates of family victimization.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of minor physical violence and severe physical violence was established according to whether these forms of violence occurred at least once during the last 12 months. As for psychological aggression, the measure of repeated acts was used as an indicator of its severity as suggested by previous studies using the PC-CTS in Quebec ( Clément et al, 2015 ; Clément et al, 2019 ; Gagné et al, 2021 ; Gagné et al, 2023 ). In fact, the original subscale of the questionnaire over-estimates the number of parents resorting to any act of psychological aggression in a year-period (e.g., yelling at the child).…”
Section: Methodsmentioning
confidence: 99%
“…A 2022 study of Manitoban parent-adolescent dyads found that 46% of the youth reported being spanked before the age of 10, although a smaller proportion of parents (39.6%) reported spanking their child (Afifi et al, 2022). A Quebec study reported that 35% of children under 17 experience physical punishment annually, and nearly 50% of children have experienced some form of psychological aggression, including being shouted or screamed at, threatened, or called names (Clément, Chamberland, & Bouchard, 2015). While previous research has shown a decline in corporal punishment among Canadian parents over time (Clément, Chamberland, & Bouchard, 2015;Fréchette & Romano, 2015), prevalence rates remain a serious public health and human rights concern, especially among individuals with a history of child welfare involvement (Trocmé & Durrant, 2003;Gilbert et al, 2011) -as well as among Canadian military and public safety personnel (including municipal and provincial police, Royal Canadian Mounted Police, correctional workers, firefighters, paramedics, and call centre dispatchers),where rates of corporal punishment in childhood are 40.3% and 46.0, respectively (Afifi et al, 2021;Turner et al, 2018).…”
Section: Conceptualization and Prevalence Of Corporal Punishmentmentioning
confidence: 99%